Uncertainty analysis of varied meshes of a finite element model using Monte Carlo simulation - Mohamad Syazwan Zafwan, Mohamad Suffian; Syahiir, Kamil; Ahmad Kamal, Ariffin (Emerald Publishing, 2022)
Purpose – Advanced computational methods help to solve complex engineering problems via finite-element simulation. However, uncertainties during the process occurred due to the nature of geometry, material properties, loading, and boundary conditions. These inaccuracies affect the accuracy of results obtained from the analysis. This paper aims to analyse the uncertainty parameters of a finite element model in Excel-Visual Basic Application (VBA) by applying a random simulation method. Design/methodology/approach – This study focuses on a finite element model with a different mesh. Young’s Modulus, E, Poisson’s ratio, and load, L are the uncertainty input parameters considered random variables. Findings – Results obtained proved that the finite element model with the most nodes and elements has better solution convergence. Originality/value – Random simulation method is a tool to perform uncertainty analysis of a finite element model.